Iowa Birdline update, March 20-26, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa Birdline updates for March 20-26, 1995. The highlights for the update include sightings of Mountain Bluebirds, Townsend's Solitaire, Cinnamon Teal and the continued presence of a female Common Eider. Also included were sightings of fifty five American White Pelicans and numerous duck species. Epson - sheet feed/flatbed